Religious Values in Hijaz Yamani Poetry: Integration of Spiritual Responsibility in Character Education - Hidayat Putra, Muhammad Adhitya; Malihah, Elly; Wiyanarti, Erlina; Darmawan, Wawan (KARSA Journal of Social and Islamic Culture, 2025)
This study aims to describe and analyze religious values â€‹â€‹and spiritual responsibility in Hijaz Yamani poems and their relevance to character education in learning. The study used a descriptive qualitative method with a content analysis approach. Data were sourced from the poetry anthology â€œMalam Hujanâ€ with data collection techniques through literature study, observation, and notes. The results of the study indicate that: (1) Religious values â€‹â€‹in Hijaz Yamani poems are integrated with spiritual responsibility values â€‹â€‹reflected through the use of diction, symbols, and figures of speech that represent the vertical relationship between humans and God; (2) The poem â€œKalau Kau Datangâ€ contains spiritual responsibility values â€‹â€‹shown through awareness of the presence of angels as a symbol of the end of life and readiness to face the Creator; (3) Religious values â€‹â€‹and spiritual responsibility in Hijaz Yamani poems have significant relevance to character education, especially in the development of studentsâ€™ spiritual, moral, and social dimensions. The implication of this study is the importance of integrating religious values â€‹â€‹and spiritual responsibility through literary works in learning to strengthen students’ character education.